(untitled) (Scientia Agropecuaria, 2024)
Root-knot nematodes are detrimental to agricultural crops and hard to control once established in the field. The objective of this research was to evaluate the growth, sporulation, and capture in vitro of asexual fungi against Meloidogyne sp. Molecular identification of the asexual fungi included in the study was performed by sequencing the ITS1 region of rDNA. The growth and sporulation of Arthrobotrys sp., Dactylellina sp. and Dactylaria sp. was evaluated in five culture media and two types of substrates (rice husks and ground corn). For the evaluation of attraction and capture of the nematodes, second stage juveniles of Meloidogyne sp. All the evaluated fungal isolates grew and sporulated in the culture media and substrates. The fungi Arthrobotrys sp. (C19-1-1) and Dactylellina sp. (C19-48) showed greater effectiveness in attracting and capturing Meloidogyne sp. The evaluated fungal isolates have the potential to colonize different culture media and substrates. In addition, they can form modified and specialized hyphae that control juvenile Meloidogyne sp. nematodes. Therefore, future studies should focus on evaluating fungal isolates against root-knot nematodes under field conditions.